(untitled) (IAHS Medical Journal, 2024)
Background: Lumbar Radiculopathy (LR) is a condition characterized by motor, reflex and sensory changes, often causing significant pain and disability. Conservative treatments are commonly recommended as initial management options. This study aims to evaluate the outcomes of various conservative treatments for LR. Materials and methods: This prospective cohort study involved 100 patients diagnosed with LR who underwent conservative treatments between January 2023 and December 2023 at our Physical Medicine Department, Institute of Applied Health Sciences (IAHS). Treatments included physical therapy, NSAIDs, epidural steroid injections and activity modification. Baseline data, including demographic information, pain intensity (VAS) functional status (ODI) and quality of life (SF-36), were collected. Follow-up assessments were conducted at 6 weeks, 3 months and 6 months. Primary outcomes were changes in VAS, ODI and SF-36 scores. Secondary outcomes included patient satisfaction and the need for additional interventions. Data were analyzed using descriptive statistics, paired t-tests and ANOVA. Results: The mean age of participants was 45.3 years, with a slight male predominance (56%). At baseline, mean VAS was 7.8, ODI was 45.6 and SF-36 was 62.5. Significant reductions in VAS (2.6), ODI (18.7), and improvements in SF-36 physical (80.3) and mental (81.7) scores were observed at 6 months (p<0.05). Patient satisfaction at 6 months was highest for epidural injections (90%), followed by NSAIDs (85%), physical therapy (80%) and activity modification (70%). The need for additional interventions decreased to 8%. The incidence of adverse events was low, with physical therapy showing the lowest rates. Initial ODI score was a significant predictor of positive outcomes (p=0.03). Conclusion: Conservative treatments for LR are effective in reducing pain and disability and improving quality of life. All treatment modalities showed comparable efficacy, with low adverse event rates, supporting their use as first-line treatments. Initial disability levels should be considered in treatment planning to optimize outcomes. Further research is needed to refine predictive models and enhance individualized treatment strategies. IAHS Medical Journal Vol 7(1), June 2024; 80-85